improvement in sperm motility viability and normality after treatment with prednisolone antisperm antibody separation and in invitro sperm activaition in immunologyically infertile men - Al-Anssari, saada; El-Yassin, hedef D.; Kanan, Z.A.; Taiyeb, A. M.; Al-Barzanchi, M.T Ridha (Journal of the Faculty of Medicine Baghdad, 2005)
Background: